Socialization and simulation of volcanic disaster response at SMK Muhammadiyah Cangkringan - Iswanto Suwarno; M. Aldi Hidayat Lamdho; Desi Eka Nuryanti; Nia Maharani Raharja; Robbi Rahim (Peneliti Teknologi Teknik Indonesia, 2023)
Dissemination of disaster response at Cangkringan Muhammadiyah Vocational School located in Argomulyo Village, Kapanewon Cangkringan, Sleman Regency. The area is not far from the Mount Merapi area, so information is needed on how to respond to disaster issues related to prevention, mitigation and preparedness. This activity was carried out as a form of UMY KKN 2023 practice in community service, especially in Argomulyo Village. The goal to be achieved in the implementation of this activity is to be able to convey information related to how to prevent, mitigate, and be prepared for a disaster that occurs. Another goal is to instill awareness in the community about the importance of early vigilance and preparedness to reduce the risk of a disaster that causes loss to the community. The method used in this activity is the socialization method by first making direct observations with the Principal of SMK Muhammadiyah Cangkringan. The targets of this service program are students of the Cangkringan Muhammadiyah Vocational School and the organizations in the school. The result of this activity is the dissemination of information and disaster management steps that can raise student awareness so that they can form a disaster care group, an organization engaged in the field of disaster.